THE CONTRIBUTION OF SAPARUIK'S MATRILINEAL RELATIVES IN FULFILLING CHILDREN'S EDUCATIONAL RIGHTS AFTER DIVORCE (CASE STUDY IN NAGARI SALAYO, KUBUNG DISTRICT, SOLOK REGENCY) - Yulfi Eranita; Fatmariza Fatmariza (UNIVERSITAS PAKUAN, 2022)
This study analyzes the fulfillment of children's education rights in divorced families related to the contribution of saparuik matrilineal relatives to the Minang Kabau family and society. This study aims to describe the contribution of saparuik matrilineal relatives in the fulfillment of children's formal education rights after their parents divorced in Nagari Salayo, Kubung District, Solok Regency. This research is a case study qualitative research. with research informants totaling 24 people. The data of this research are the results of interviews with parents or matrilineal relatives of Saparuik, religious court clerks, and the guardians of Nagari Salayo, the head of Jorong, and the surrounding community. The data collection technique in this study used interview, observation, and documentation techniques and was analyzed by steps such as: data reduction, data presentation, and drawing conclusions. The findings of the study indicate that the fulfillment of children's education rights after divorce in Nagari Salayo has been partially fulfilled which can be seen from 8 samples of divorced families consisting of seven women's families, namely mothers and grandmothers, and one male family, namely fathers, women are more responsible. responsible for the continuation of their children's education after divorce than men. Therefore, it can be concluded that the saparuik matrilineal relatives contribute to the fulfillment of children's educational rights after the divorce occurs, this can be seen in the role or contribution of grandmothers, sisters from the mother's side and also the mother of the children resulting from the divorce where the cultural background of the Minangkabau adheres to the system. Matrilineal kinship is very visible in the post-divorce parenting pattern.